CULTURAL AND BIOCLIMATIC INSIGHTS FROM THE VERNACULAR ARCHITECTURE OF THE CASBAH OF ALGIERS: A MODEL FOR SUSTAINABLE FUTURE - Roufaida Benbrahim; Leila Sriti (International Journal of Innovative Technologies in Social Science, 2025)
The Casbah of Algiers, a UNESCO World Heritage site, exemplifies the ingenuity of Mediterranean vernacular architecture and the enduring interplay between built form, climate, and culture. This study explores the bioclimatic principles inherent in the urban fabric and architectural typologies of the Casbah, emphasizing their relevance to sustainable design in Mediterranean climates. It examines how traditional construction techniques, spatial organization, and local materials optimize thermal comfort and energy efficiency while supporting vibrant cultural and social practices. Through on-site observations, photographic documentation, and an examination of socio-cultural dynamics, the research assesses the resilience of the architecture and community of the Casbah. The findings highlight the effectiveness of compact urban morphology, shaded courtyards, thick masonry walls, and community-centred spaces in providing passive cooling, fostering social cohesion, and conserving energy, thereby reducing dependence on mechanical systems. The study advocates integrating these bioclimatic and cultural strategies into contemporary urban design to create resilient and environmentally harmonious spaces that honour cultural heritage while addressing modern challenges. By bridging traditional knowledge, social practices, and modern approaches, this research contributes to the discourse on sustainable development, underscoring the enduring value of vernacular architecture for climate-responsive, socially inclusive, and culturally rooted design solutions.